ANALISIS PEMASARAN PRODUK LAYANAN HOMEVISIT PASIEN GANGGUAN JIWA DI RUMAH SAKIT JIWA : ARTICLE REVIEW - Gunata, Ivan Paulus (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
In 2018, the World Health Organization (WHO), in its report titled "Mental Health Action Plan," stated that explained that around 300 million people in the world suffer from depression, 60 million people in the world suffer from bipolar affective disorder, and 23 million people have psychosis. Meanwhile, in Indonesia, based on data from Riskesdas 2018 data on sufferers of mental disorders among the Indonesian population aged 15 years and over, there are 6.1 percent suffer from depression, and there are 9.8 percent suffer from emotional mental disorders due to stress. Stressors that are handled well will provide positive emotions. There is an essential difference between positive and negative emotions: they have separate bases in brain chemistry and can coexist but have different functions. Positive emotions can eliminate the physiological effects of negative emotions and reduce sympathetic nervous system activity to baseline. Stressors from psychosocial factors greatly influence patient recovery, where these stressors cannot necessarily be handled in health facilities. Home Visits to the patient's residence and correcting stressors around the patient can improve symptoms and complete the patient's healing.